How many men did you sleep with before me? An auto-ethnography on gender violence - Silba, Malvina Leonor (2017)
This article is a first-person account of gender violence that utilizes auto-ethnography as a methodological and narrative tool. In the article, the author analyzes a relationship with a violent man in which two differences, class and gender, functioned as hierarchies. By analyzing certain moments of this relationship from the perspective of gender theory, the author intends to provide insight into the complex and often contradictory features of the gender violence suffered by women in different regions of the world and in a range of social and cultural contexts. This personal story and the connections with the stories of other women in her family – themselves victims of gender violence and the same social hierarchies – allow the author to analyze the mandates for women in a patriarchal society. Finally, the article narrates the strategies of empowerment that she was able to construct in certain contexts, distinguishing individual and collective empowerment as a key analytical but also political concept in the struggle against gender violence.